Where Sepsis and Antimicrobial Resistance Countermeasures Converge - Inglis, Timothy J. J.; Urosevic, Nadia (Frontiers in Public Health, 2017)
The United Nations General Assembly debate on antimicrobial resistance (AMR) recognises the global significance of AMR. Much work needs to be done on technology capability and capacity to convert the strategic intent of the debate into operational plans and tangible outcomes. Enhancement of the biomedical science-clinician interface requires better exploitation of systems biology tools for in-laboratory and point of care methods that detect sepsis and characterise AMR. These need to link sepsis and AMR data with responsive, real time surveillance. We propose an AMR sepsis register, similar in concept to a cancer registry, to aid coordination of AMR countermeasures.